НЛП: норма или манипуляция сознанием? - Арнаут, В. А.; Стрельцова, Н. Г. (ХНУРЭ, 2012)
When it comes to neuro-linguistic programming, it is understood that exposure to that meter is not something shameful. This is the norm for the species "Homo sapiens". Human being is born with a minimal set of innate behavioral programs, and his personality is formed in the process of communicating with other people and it is through NLP. And where else to take the set of behaviors, which allows a person to exist in society?